The Current State of Orthopaedic Educational Leadership. Issue 4 (15th February 2021) - Bi, Andrew S.; Fisher, Nina D.; Singh, Sameer K.; Strauss, Eric J.; Zuckerman, Joseph D.; Egol, Kenneth A.
Abstract : Introduction: It is important to understand the current characteristics of orthopaedic surgery program leadership, especially in the current climate of modern medicine. The purpose of this report was to describe the demographic, academic, and geographic characteristics of current orthopaedic chairs and program directors (PDs). Methods: Orthopaedic surgery residency programs were obtained from the Accreditation Council for Graduate Medical Education website and cross-referenced with the Electronic Residency Application Service, identifying 161 residency programs for the 2018 to 2019 cycle. All data were collected in January 2020 to best control for changes in leadership. Demographic and academic information were collected from public websites. For geographic analysis, the United States was divided into five regions, and training locations were categorized as appropriate. Results: A total of 153 chairs and 161 PDs were identified. 98.0% of chairs were men versus 88.8% of PDs ( P = 0.001). Chairs had been in practice and in their current position for longer than PDs (26.4 vs 16.8 years [ P < 0.005] and 9.1 vs 7.1 years [ P = 0.014], respectively). Chairs had more publications and were more likely to be professors than PDs. PDs were more likely to remain at both the same region and institution that they trained in residency. The most common subspecialty was sports among chairs and trauma among PDs, although when compared with national averages orthopaedic trauma and orthopaedic oncology were the most overrepresented subspecialties. Conclusion: Orthopaedic chairs are more likely to be men, have had longer careers, and have more academic accomplishments than their PD counterparts. Geography appears to have an association with where our leaders end up, especially for PDs. Subspecialization does not notably influence leadership positions, although orthopaedic trauma and orthopaedic oncology surgeons are more commonly represented than expected. This report serves to identify the current state of orthopaedic leadership and may provide guidance for those who seek these leadership positions.